2017
DOI: 10.12911/22998993/66249
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Soil Conditioners on Cellulose, Hemicellulose, and the Adl Fibre Fraction Concentration in Dactylis Glomerata and Lolium Perenne

Abstract: Replicated three times, the research was conducted in the experimental field between 2011 and 2014. Three soil conditioners with the following trade names: UGmax, EkoUżyźniacz, and Humus Active Papka were used in the experiment, separately or together with NPK fertilisers. They were all used on plots sown with two species of grass, Dactylis glomerata of the Bora variety and Lolium perenne of the Info variety. The plant material from both grass species was tested for the concentration of ADL fraction (% DM), ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 1 publication
0
13
2
Order By: Relevance
“…Additionally, Ciepiela (2014) found in her studies that the Kelpak biostimulant increased the hemicellulose content of Festulolim braunii, but an interaction of this product with N resulted in a decrease. In addition, Ciepiela (2014) and Truba et al (2017) recorded the lowest hemicellulose content in the first growth cycle, but the results obtained in the present studies showed that the differences were not statistically significant.…”
Section: Discussioncontrasting
confidence: 79%
See 3 more Smart Citations
“…Additionally, Ciepiela (2014) found in her studies that the Kelpak biostimulant increased the hemicellulose content of Festulolim braunii, but an interaction of this product with N resulted in a decrease. In addition, Ciepiela (2014) and Truba et al (2017) recorded the lowest hemicellulose content in the first growth cycle, but the results obtained in the present studies showed that the differences were not statistically significant.…”
Section: Discussioncontrasting
confidence: 79%
“…The trend of changes in cellulose amounts across harvests in Ciepiela's (2014) studies was confirmed by the results of the present experiment as its highest content was recorded in the first harvest and the smallest in the third. In the studies of Truba et al (2017) soil conditioners used on their own also increased cellulose content, but mineral fertilizers reduced it. Weather conditions in both growing seasons, not conducive to the proper growth and development of grasses, were also of great importance for the formation of cellulose content.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sosnowski (2012), applying both UGmax and mineral fertilizer, observed that Lolium perenne responded with a significant increase in the number of shoots, leaf lamina length, leaf base width, and leaf greenness index. Additionally, Truba et al, (2017), also in an experiment with Lolium perenne, found the lowest biomass increase when Humus Active Papka was applied on its own. In the present experiment, comparing the effects of the soil conditioners on all grass species, UG-max and Substral had the highest impact on lawn appearance (7.9 o ) and Humus the lowest (6.4 o ).…”
Section: Lawn Appearance In Summermentioning
confidence: 89%